Review Komprehensif : Studi Perbandingan Antara Material Logam dan Komposit untuk Pembuatan Helm Anti Balistik - Miwazuki, Shella Athaya; Anisa, Puspita; Rustama, Ravania Zackeisha; Christina, Athalia; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2024)
The need to develop protective systems to protect against attacks from various sources is increasingly becoming a personal, social and national security issue. To develop innovative armor systems, it is necessary to monitor the developments made on the types, technology and performance of threats (weapons, projectiles, explosives, etc.) In particular, the use of helmets of a high level of protection on the battlefield is essential. Therefore, the development of evaluation methods that can predict injury and trauma is very important. However, the risk of injury or trauma that may result from induced acceleration is an additional consideration. To develop new materials and layouts for helmets, it is necessary to study the impacts caused by ballistic impacts on the human head in various scenarios. Composite materials in military applications have proven to be superior to metal materials, in increasing the mobility of Force personnel. The use of composite materials in military helmets is very important in relation to the speed of incoming bullets, one of which is made from thermoplastic and thermoset polymers. Particle composite material composed of Bisphenol A epoxy resin matrix and reinforcement in the form of Javanese jute fiber which is applied to bulletproof helmets. When using this composite, you can determine the number of sheets of Javanese jute fiber that is effective against the force of the bullet fired, this is to support the safety of its use.